1983
DOI: 10.1007/bf02372188
|View full text |Cite
|
Sign up to set email alerts
|

Eggs of stored-product lepidoptera as hosts forTrichogramma evanescens [Hym.: Trichogrammatidae]

Abstract: Eggs were collected from Anagasta kiiehniella (Zeller), Ephest~a cautella (Walker), E. elutella, (Hiibner), E. figulilella (Gregson), and Plodia interpunctella (Hiibner) and exposed to adults of the egg parasite, Trichogramma evanescens Westwood, in a free choice experiment. Host eggs were ranked by decreasing percentages of parasitization as follows : E. elutella > E. cautella > E. figulilella > A. kiiehniella > P. interpunctella. Differences in percent parasitization were not significant between Ephestia spp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
3

Year Published

1990
1990
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 20 publications
1
12
0
3
Order By: Relevance
“…Bracon hebetor Say (Hymenoptera: Braconidae) and Venturia canescens (Gravenhorst) (Hymenoptera: Ichneumonidae) attack the larvae of stored product moths (Keever et al, 1985;Cline et al, 1986). Trichogramma pretiosum Riley (Hymenoptera: Trichogrammatidae) attacks the eggs of stored product moths (Brower, 1983). Peregrinator biannulipes Montrouzier et Signoret (renamed from Allaeocranum biannulipes) (Hemiptera: Reduviidae), which is known as the assassin bug found in warehouses and under tree bark in tropical regions (Hill, 1990;Takahashi and Nishi, 2003), attacks the larvae or eggs of stored product insect pests (Awadallah and Afifi, 1990).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bracon hebetor Say (Hymenoptera: Braconidae) and Venturia canescens (Gravenhorst) (Hymenoptera: Ichneumonidae) attack the larvae of stored product moths (Keever et al, 1985;Cline et al, 1986). Trichogramma pretiosum Riley (Hymenoptera: Trichogrammatidae) attacks the eggs of stored product moths (Brower, 1983). Peregrinator biannulipes Montrouzier et Signoret (renamed from Allaeocranum biannulipes) (Hemiptera: Reduviidae), which is known as the assassin bug found in warehouses and under tree bark in tropical regions (Hill, 1990;Takahashi and Nishi, 2003), attacks the larvae or eggs of stored product insect pests (Awadallah and Afifi, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Biological control is thus being regarded with increasing interest, since it is nontoxic and does not damage human health or the environment. The use of natural enemies (predators and parasitoids) has been studied by various researchers for storedproduct insect pests (Brower, 1983;Keever et al, 1985;Cline et al, 1986;Awadallah and Afifi, 1990;Wen and Brower, 1994;Donnelly and Phillips, 2001;Nishi and Takahashi, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Investigations were carried out in the laboratory (e.g. Brower, 1983;Fye & Larsen, 1969) as well as in the field (e.g. Ashley et al, 1974;Boldt et al, 1973), and preference was usually inferred from the numbers of hosts found parasitized.…”
Section: Introductionmentioning
confidence: 99%
“…Hassan (1997) indicó que varias especies del parasitoide han sido liberadas anualmente en más de 16 millones de hectáreas de cultivos anuales y perennes en contra de insectos plaga del orden Lepidoptera. La utilización de las especies de Trichogramma ha sido favorecida debido a la facilidad de realizar crías masivas en el laboratorio utilizando como hospederos los huevos de Sitotroga cerealella (Olivier) (Lepidoptera: Gelechiidae) (Brower 1983, Corrigan & Laing 1994.…”
Section: Palabras Clave: Sitotroga Cerealella Spodoptera Frugiperdaunclassified